2011
DOI: 10.1038/jp.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the appropriate neonatal resuscitation device for village midwives

Abstract: Objective: An appropriate neonatal resuscitation device for village midwives in Indonesia is chosen.Study Design: The study compared four neonatal resuscitation devices: Ambu neonate bag and mask, Topster bag and mask, Laerdal pediatric pocket mask and Tekno tube and mask. Functionality was tested by 40 village midwives who were also interviewed about ease of use. Ventilation volume was tested using a mannequin and computer interface. Other features were assessed by PATH engineers.Result: There was no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However given that prehospital care providers may consider mouth-to-mouth ventilation unacceptable for regular use, a pocket mask with oxygen inlet was suggested [160], even though ventilation using a pocket mask was described as difficult. Three studies showed that adequate ventilation with mouth to mask on children was performed in between only 40- 75%, depending on the type of pocket mask devices being used [161,162] and with 20% of excessive pressure breaths [163]. …”
Section: Resultsmentioning
confidence: 99%
“…However given that prehospital care providers may consider mouth-to-mouth ventilation unacceptable for regular use, a pocket mask with oxygen inlet was suggested [160], even though ventilation using a pocket mask was described as difficult. Three studies showed that adequate ventilation with mouth to mask on children was performed in between only 40- 75%, depending on the type of pocket mask devices being used [161,162] and with 20% of excessive pressure breaths [163]. …”
Section: Resultsmentioning
confidence: 99%
“…Two surveys (Ariawan et al, 2011;Coffey, Kelly & Tsu, 2007) reported the views of health care providers on the use of bag and mask and tube and mask in neonatal resuscitation. One of these surveys (Coffey, Kelly & Tsu, 2007) reported that bag and mask is much easier to use than tube and mask as the latter requires the user to constantly bend forward and blow for 10 to 15 minutes.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Little et al [62 & ] remind us that the majority of the burden of illness and therefore the largest potential gains are to be found in the developing world. Research into devices which meet the specific needs of developing countries has started to occur [64,65], but much more needs to be done in order to meet the United Nations Millennium Development Goal of reducing the child mortality rate by two-thirds by 2015 [66]. Essential Newborn Care training in universal precautions, routine neonatal care, resuscitation, thermoregulation, breastfeeding and kangaroo care almost halved 7-day mortality in 18 low-risk Zambian centres [63].…”
Section: Resuscitation In Developing Countriesmentioning
confidence: 99%